Kesulitan Berbahasa Indonesia Dalam Konteks Pembelajaran Tematik Kelas VI B di MIS At-Taqwa Sambas - Solehshi, Vianita; Putra, Purniadi; Effiyadi (putrapublisher.org, 2024)
This research was conducted because there were difficulties among some of the class VI B students at the At-Taqwa Sambas Private Madrasah Ibtidaiyah. The difficulties experienced by students in learning were 4 students having difficulty listening, 2 students having difficulty reading, for speaking skills students had difficulties such as lack of confidence. Fear and embarrassment arose due to teasing and lack of mastery of the language, then 5 students experienced difficulty in writing. The aim of this research is to describe and analyze the difficulties experienced by students in Indonesian language skills, the contributing factors, and the strategies used by teachers to overcome the difficulties experienced by students. This research uses a qualitative approach with a case study type. The results of the research are the difficulties experienced by students in speaking Indonesian during class VI B thematic learning at the At-Taqwa Private Madrasah Ibtidaiyah, namely difficulties in listening skills, difficulties in reading skills, difficulties in writing skills, difficulties in speaking skills. Factors that contribute to students' difficulties in speaking Indonesian during class VI B thematic learning at the At-Taqwa Private Madrasah Ibtidaiyah are internal factors and external factors, internal factors come from within the student such as lack of self-confidence and external factors come from outside the student such as the environment child friendship. Strategies that can be implemented to help students overcome Indonesian language difficulties in class VI B thematic learning at the At-Taqwa Private Madrasah Ibtidaiyah are getting used to reading first before starting learning activities, communicating a lot with parents regarding student learning activities at home, and creating activities. discussion then presents the results of the discussion in front of the class to practice students' speaking skills and increase students' self-confidence